The Relationship of Knowledge and The Role of Cadres in Handling Mental Disorder in The Working Area of Kedungwuni II Primary Health CareR - Nafiah, Hana; Dzil K, Aisyah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
Mental disorder are the conditions with psychiatric malfunctioning including thought process, emotion, volition, and psychomotor behavior. Mental health cadres have an important role in the effort to deal with mental disorder in the community. Knowledge has an influence on the ability of cadres to carry out role in the community. The aim of this study was determine the relationship between knowledge and the role of cadres in handling mental disorder in the working area of Kedungwuni II Primary Health Care. The research method used correlative study, to correlate knowledge and role variable. Sample in this study where 71 cadres in the working area of Kedungwuni IIn Primary Health Care who appropriate inclusion criteria. Result of this study showed that most of the cadres 41 people (57,7%) have good knowledge and 42 people (59,1%) have a good role in handling mental disorder. The result of data analyzed showed that there was significant relationship between knowledge and the role of cadres in handling mental disorder in the working area of Kedungwuni II Primary Health Care with p value =0.010 (p value < 0.05). Refresher on cadres training on handling mental disorder need to updating cadres’ knowledge so that mental disorder services in the primary level can be handle optimally. Keywords: knowledge; role of cadres; caring for mental disorder